Clinical simulation in an objective structured clinical examinations scenario active learning improved communication skills and assessment of psychopharmacology student of medicine degree. - Bellido-Estévez, Inmaculada; Blanco-Reina, Encarnación; Gómez-Luque, José Aurelio (20th WPA World Congress of Psychiatry, 2021)
Objective: Objective Structured Clinical Examinations are versatile multipurpose evaluative tools utilized to assess health care professionals in a clinical setting including communication skills and ability to handle unpredictable patient behavior. Clinical simulation-based training is a widespread strategy to improve health-care quality. We aim to evaluate the impact of clinical simulation (CS) performed in an objective structured clinical examinations (OSCEs) scenario designee and perform by student on arguing, planning capacities, communication skills and learning of therapeutics in undergraduate students from Psychopharmacology course of the Medicine Degree. Methods: A two-year study in which undergraduate students from Medicine degree’s Psychopharmacology course were trained using CS in an OSCEs scenario designee and perform by students, including: Explain a treatment, convince of the need to follow a treatment, warn of possible adverse reactions, report a death due to an medicine adverse reaction. Data from students of previous courses who never run CS-OSCEs were use as control. Results: Students from Psychopharmacology course, N=331, 60.7% female, 21±4.5 years old, were enrolled. The average time spent by students in making CS-OSCE training was 12.6±3.1 h. The percentage of students that were satisfied with this way of active learning was 92.5%. CS-OSCE student group showed an increased number of correct answer to the questions of the assessment with respect to non-CS-OSCE trained students +26.9% hits (P < 0.05). Conclusion: Clinical simulation active learning in an objective structured clinical examinations scenario designed and performed by student of Psychopharmacology of the Medicine Degree improved their communication skills and knowledge of medicines.
Abstrac congreso
Keywords: Psiquiatría - Congresos; Clinical simulation; Objective structured clinical examinations; Active learning; Communication skills; Assessment